1968
DOI: 10.3758/bf03342398
|View full text |Cite
|
Sign up to set email alerts
|

Dominance behavior in socially isolated rats

Abstract: Male rats, socially isolated from 14-90 days of age, were found to be dominant over socially raised littermates when competing for food. The effect was attributed to the development of a response hierarchy during isolation which favored winning in the particular competition situation used in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Experiment 2 was specifically designed to examine the effects of familiarity as well as social experiences on immature fighting. Both isolation (Ward & Gerall, 1968) and unfamiliarity (Calhoun, 1948) increase conflict in adult male rats, and these factors appear to increase juvenile conflict as well. The young animals that were observed with relatively unfamiliar conspecifics were notably more active socially than familiar juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment 2 was specifically designed to examine the effects of familiarity as well as social experiences on immature fighting. Both isolation (Ward & Gerall, 1968) and unfamiliarity (Calhoun, 1948) increase conflict in adult male rats, and these factors appear to increase juvenile conflict as well. The young animals that were observed with relatively unfamiliar conspecifics were notably more active socially than familiar juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…Our rats with many wins in the runway test crossed the alley slowly during training and frequently boxed during competition (Table 2). A correlation between training success and test results was also shown by Ward and Gerall (1968) in the same system. Runway-dominant rats showed frequent "freezing" (Spigel & Fraser, 1974), that is, a motionless position as a result of a species-specific defense reaction (Timmermans, 1978) as a form of boxing.…”
Section: Discussionmentioning
confidence: 81%
“…Baenninger (1967) suggested that social responses such as grooming, chasing, and sniffing were made to the rat's own tail because the tail was the only stimulus that moved in relation to the environment with apparent spontaneity. The similarity between tail manipulation observed in isolated rats and the activity of lactating females whose pups had been removed, observed in the present study and in Weisner and Sheard (1933), should receive further examination. Should juvenile isolation from peers and maternal isolation from offspring manifest other similarities, the latter could serve as a useful paradigm for the study of social deprivation.…”
Section: Discussionmentioning
confidence: 99%